A educação 4.0 à luz da teoria crítica da tecnologia de Andrew Feenberg - Norte, Andréa Pereira (2021)
Based on Andrew Feenberg's theoretical framework of philosophy of technology, the resulting dissertation is a reflection on Education 4.0, thus understood as being related to the moment of the 4th Industrial Revolution that marks the current stage of global society. The critical theory of technology, as developed by Feenberg, is then based on sources, a theory that adds value-laden aspects of technology to the neutral aspects of technology, thus expanding the discussion to the scope of democratic participation in the choice and development of media systems. alternative purposes. It then pursues the objective of performing an analysis and interpretation of technology in the human condition and its consequences in Education 4.0 and from there on debating possible paths for education to follow, going beyond the passive reception of artifacts, participating, in a democratic way, in the definition and choice of them. The dissertation was carried out through a bibliographic review of books, articles, theses, and dissertations. Characterized the profile of the 4th. Industrial Revolution, characteristic of the current moment, makes explicit the resulting metamorphosis of education, with a view to establishing a proposal for new directions for it, in the light of Feenberg's theoretical categories.